Toxicity assessment of metallic nanoparticles on aquatic biota - Nunes, Pedro Miguel Xavier (2021)
The recent increase in the use of nanomaterials in the day-to-day context, is due to the emergence and development of the nanotechnology from the mid1980s when their bases began to be established. From this point onwards, there was a great interest of the scientific community to explore this new type of material with interesting and promising properties, given its high resistance, reduced size, anti-microbial properties, ease of synthesis, among many others. With advances in this field, these materials have become of common usage and now have multiple applications not only in the most varied fields of science, but also in practical life, where they began to integrate personal hygiene products, containers, infrastructures, food and even part of biomedical techniques in the treatment of cancer or in simple MRI scans. In this context, this study aimed at evaluating the influence of chemical composition and coating in the ecotoxicity of iron superparamagnetic nanoparticles (NPs) to freshwater biota. For this, two iron NPs coated with dopamine were selected to be studied: iron (II) selenide (Fe3Se4@Dopa) and iron (II) oxide (Fe3O4@Dopa). To assess the influence of coating in the toxicity of NPs, Fe3Se4 was also produced with levadopamine as a coating agent (Fe3Se4@Levodopa). For each of the NPs the following toxicity assays were carried out: 72-hour growth inhibition assay with the green alga Raphidocellis subcapitata, 7-day growth inhibition assay with the macrophyte Lemna minor, 24-hour mortality assay with rotifer Brachionus calyciflorus, 72-hour mortality and feeding inhibition with the cnidarian Hydra viridissima, and 96-hour embryo development assay with Xenopus laevis. No clear pattern of toxicity was observed in the tested nanoparticles. Per example, nanoparticles presenting less toxicity for the microalgae and hydras were the Fe3Se4@Levodopa ones, but this was the NP most toxic for L. minor. The species presenting higher sensitivity for all three tested nanoparticles was the rotifera B. calyciflorus, exhibiting significant mortality in concentrations of 17.6 mg/L. Although there is no information in scientific literature on expected concentrations of the NPs occurring in surface waters, based on previsions performed on other nanoparticles used more commonly in human products, it is expected that concentrations that induced effects on the present study (in orders of mg/L) are far above those that may occur in the environment in the near future.